Ask Your Question

Revision history [back]

Wrong factorization of expressions containing exponentials ?

Is there something wrong with the factorization of expressions containing exponentials ? I obtain the following strange results (Sagemath 8.6):
factor(exp(-x)+2exp(x)) ---> 3e^x,
factor(exp(-x)+xexp(-x)) ---> (x + 1)e^x Any suggestions welcomed.

Wrong factorization of expressions containing exponentials ?

Is there something wrong with the factorization of expressions containing exponentials ? I obtain the following strange results (Sagemath 8.6):
factor(exp(-x)+2exp(x)) factor(exp(-x)+2*exp(x)) ---> 3e^x,
factor(exp(-x)+xexp(-x)) factor(exp(-x)+x*exp(-x)) ---> (x + 1)e^x Any suggestions welcomed.

Wrong factorization of expressions containing exponentials ?

Is there something wrong with the factorization of expressions containing exponentials ? I obtain the following strange results (Sagemath 8.6):
factor(exp(-x)+2*exp(x)) ---> 3e^x, 3*e^x,
factor(exp(-x)+x*exp(-x)) ---> (x + 1)
e^x 1)*e^x Any suggestions welcomed.

Wrong factorization of expressions containing exponentials ?

Is there something wrong with the factorization of expressions containing exponentials ? I obtain the following strange results (Sagemath 8.6):
factor(exp(-x)+2*exp(x)) ---> 3*e^x,
factor(exp(-x)+x*exp(-x)) ---> (x + 1)*e^x

Any suggestions welcomed.

Wrong factorization of expressions containing exponentials ?

Is there something wrong with the factorization of expressions containing exponentials ? I obtain the following strange results (Sagemath 8.6):
factor(exp(-x)+2*exp(x)) ---> 3*e^x,
factor(exp(-x)+x*exp(-x)) ---> (x + 1)*e^x

Any suggestions welcomed.

Wrong factorization of expressions containing exponentials ?

Is there something wrong with the factorization of expressions containing exponentials ? I obtain the following strange results (Sagemath 8.6):
factor(exp(-x)+2*exp(x)) ---> 3*e^x,
factor(exp(-x)+x*exp(-x)) ---> (x + 1)*e^x

Any suggestions welcomed.